Musicians’ Personal Branding Strategies in Live Music Performances at Summarecon Mall Bandung - Teuku Rizky Putra Vidrian; Sandie Gunara; Fensy Sella (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Purpose: This study aims to explore the personal branding strategies of musicians in live music performances within commercial public spaces, focusing on performances at Summarecon Mall Bandung. The research examines how musicians maintain their musical identity and personal branding when performing under genre regulations determined by mall management. Method: This research employs a qualitative approach using a multi-case study method. The research subjects consist of two bands that regularly perform at Summarecon Mall Bandung, namely Band Miracle and Band Soundmate. Data were collected through direct observation of live music performances, structured interviews with 14 band members, and interviews with approximately 30 mall visitors who attended the performances. Supporting data in the form of photographs, videos, and song setlists were also utilized. Data analysis was conducted using thematic analysis, and data validity was ensured through source and technique triangulation. Results and Discussion: The findings indicate that musicians’ personal branding in live music performances is not solely determined by musical genre, but is strongly shaped by performative strategies, audience interaction, and musicians’ attitudes toward performance regulations. Band Miracle emphasizes energetic stage performance, intensive audience interaction, and selective song rearrangements, while Band Soundmate constructs personal branding in a more flexible and organic manner through casual communication and relaxed stage presentation. Conclusion: Live music performances in shopping malls function as both strategic and challenging spaces for musicians in maintaining personal branding. Despite genre restrictions, musicians are able to preserve their musical identity through adaptive performance strategies and meaningful audience engagement.